UPAYA MENINGKATKAN HASIL BELAJAR SISWA KELAS IV PADA MATERI IPAS MELALUI MODEL PEMBELAJARAN PBL BERBANTUAN MEDIA FLIPBOOK DI SD NEGERI KANIGORO 1 - Atika Femylia Putri; Nurlita Yuniarsih; Dita Fitriyah Gultom; Melik Budiarti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research was conducted basically to improve student learning outcomes in the subject of science, namely by implementing a problem-based learning model using Flipbook media. The problems in this research were found during the implementation of the Pre-cycle observation carried out at SDN Kanigoro 1 in grade IV students. At the beginning of learning, cases were identified, including the use of inappropriate learning media, teachers only used the lecture method, only 4 out of 12 students completed the science learning material. The classroom action approach used in this research was carried out in two cycles including the planning, implementation, observation, and reflection stages. The subjects of this research were 12 students from grade IV Kanigoro 1. The data analysis technique used was quantitative descriptive. The data collection instrument in this research was a learning outcome test. The results showed that the use of the PjBL model combined with Flipbook media was able to provide a significant increase in student learning achievement. The pre-action results showed low student learning outcomes with learning completion of 0% of the total 12 students. Student learning achievement then increased in cycle I to 16% and in cycle II to 100%. Based on these findings, it can be concluded that the PBL learning model supported by Flipbook media is effectively used as an alternative approach to improve the learning achievement of fourth grade students at SDN Kanigoro 1. The combination of this model and media has the potential to make science learning fun and student-centered.